2017
DOI: 10.1097/prs.0000000000003384
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Fat Pad Augmentation for Facial Rejuvenation

Abstract: The buccal space, with its fat pad, is a valuable, overlooked target in facial rejuvenation procedures. The authors identified a specific group of patients who have normal or prominent malar projection in the presence of atrophy of the buccal fat pad, with or without prominent gonial angles. Eight of 24 prospectively studied patients (Biomedical Research Institute of America) who had fat grafts and face lifts received an average of 2.7 ml of fat transferred into the buccal space. Immediate visual correction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…The buccal fat pad is an often-overlooked component to the youthful midface and should be complementarily reconstituted after malar augmentation to prevent a hollowed appearance. 12,14 Lower Third Primary features of the lower third of the face include the nasolabial fold, labiomandibular fold (marionette lines), prejowl sulcus (geniomandibular groove), labiomental sulcus, lips, and chin. Deepening of the nasolabial fold occurs with deflation of the cheek.…”
Section: Middle Thirdmentioning
confidence: 99%
“…The buccal fat pad is an often-overlooked component to the youthful midface and should be complementarily reconstituted after malar augmentation to prevent a hollowed appearance. 12,14 Lower Third Primary features of the lower third of the face include the nasolabial fold, labiomandibular fold (marionette lines), prejowl sulcus (geniomandibular groove), labiomental sulcus, lips, and chin. Deepening of the nasolabial fold occurs with deflation of the cheek.…”
Section: Middle Thirdmentioning
confidence: 99%
“…On the contrary, given the fuller appearance of the young face, it has recently been suggested that lipofilling is performed to enhance BFP fullness during face lifting procedures. 11 As such, the appropriateness of BFP procedures should be determined on a case-by-case basis, depending on the particular age-associated changes observed in a given patient.…”
Section: Resultsmentioning
confidence: 99%
“…The technique begins with a specific topographical facial assessment for all areas of volume loss and contour deficiencies; then these areas can be treated using two to three different size and types of fat grafts. One is a millifat parcel of 1.5 to 2.0 mm used for deep compartment and bone losses; the second, a microfat parcel of 1.0 mm, used for superficial fat losses above the facial musculature and in buccal fat pad if deficiency exists ; and the third is a cellular optimized nanofat made with LipocubeNano. Nanofat is administered in the ITR 2 using several methods including syringe delivery, automated delivery, microneedling with a variety of devices, and compounding the nanofat into a unique nanofat biocreme.…”
Section: Enzyme‐free Methods Of Adipose Tissue Processingmentioning
confidence: 99%